Sección 3 de las Normas Internacionales de Información Financiera para PyMES y su impacto en la representación fiel de los Estados Financieros de la empresa CORDIALSA. - Totoy Ugsiña, Katheryn Estefania (2025)
This research aims to analyze the impact of implementing the International Financial Reporting Standards, specifically Section 3 of the standard for small businesses, as stipulated by the supervisory bodies, based on the financial statements of the company CORDIALSA for the last three years. This accounting standard focuses on the disclosure of information about each item that comprises each statement, in compliance with several accounting principles, particularly those of accrual, going concern, uniformity, comparability, and relative importance. These principles aim to enhance the quality and relevance of the financial information presented to users. The researcher will investigate how the adoption of this regulation affects the clarity, comparability, and usefulness of financial statements, as well as the perception of stakeholders regarding the company's financial risk management and decision-making processes. A quantitative approach will be employed, utilizing financial statements as the basis for information and verifying the application of international standards. This approach will identify taxable or deductible temporary differences, the vast majority of which accurately reflect transactions in a real-world manner, thereby approximating the company's reality. Additionally, changes in key transparency indicators before and after implementation will be evaluated, highlighting the importance of adhering to international standards to strengthen investor confidence and inform strategic decision-making.